2007
DOI: 10.1089/hum.2006.145
|View full text |Cite
|
Sign up to set email alerts
|

Effective Treatment of Human Breast Tumor in a Mouse Xenograft Model with Herpes Simplex Virus Type 1 Specifying the NV1020 Genomic Deletion and the gBsyn3 Syncytial Mutation Enabling High Viral Replication and Spread in Breast Cancer Cells

Abstract: A new oncolytic and fusogenic herpes simplex virus type 1 (HSV-1) was constructed on the basis of the wildtype HSV-1(F) strain. To provide for safety and tumor selectivity, the virus carried a large deletion including one of the two alpha4, gamma(1)34.5, alpha0 genes and the latency-associated transcript region. The gamma(1)34.5 gene, a major neurovirulence factor, was replaced by a gene cassette constitutively expressing the red fluorescent protein gene. Homologous recombination was used to transfer the fusog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 67 publications
(79 reference statements)
1
30
0
Order By: Relevance
“…Thus, oncolytic HSV-1 may be effective both directly as a cancer killing agent and indirectly as an immunological enhancer, or in situ cancer vaccine (13,49). Previously, we reported that the novel fusogenic oncolytic herpesvirus OncSyn (OS) was effective at treating primary solid breast tumors in mice (25,26). Moreover, treatment of primary 4T1 tumors in syngeneic BALB/c mice with OS led to a substantial reduction in the formation of metastatic foci within multiple organs and in some cases eliminated lung metastasis, suggesting the development of effective antitumor immunity (43).…”
mentioning
confidence: 99%
“…Thus, oncolytic HSV-1 may be effective both directly as a cancer killing agent and indirectly as an immunological enhancer, or in situ cancer vaccine (13,49). Previously, we reported that the novel fusogenic oncolytic herpesvirus OncSyn (OS) was effective at treating primary solid breast tumors in mice (25,26). Moreover, treatment of primary 4T1 tumors in syngeneic BALB/c mice with OS led to a substantial reduction in the formation of metastatic foci within multiple organs and in some cases eliminated lung metastasis, suggesting the development of effective antitumor immunity (43).…”
mentioning
confidence: 99%
“…Although the results of clinical trials have shown that these types of oncolytic HSV can safely be administered to humans, there is significant room for improvement in treatment efficacy, which is hampered, at least in part, by the reduced capacity of these viruses to replicate in tumor cells (69). Several groups of investigators have sought to take advantage of cell-cell fusion mechanisms to overcome the problem and have reported that syncytial mutations can enhance the potency of oncolytic HSV either or both in vitro and in vivo (52)(53)(54)(55). Since transductional targeting diminishes the dependence of oncolytic HSV on attenuating mutations for safety, our observations that gD retargeting does not interfere with syncytium formation by gB and gK syn mutants and that even a combination of syn mutations does not abolish the strict dependence of infection on the target receptor suggest that retargeted syn mutant HSV may offer oncolytic activity superior to that of the previous oncolytic syn mutant HSV strain.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have demonstrated that the antitumor activity of various types of oncolytic HSV can be enhanced by syncytial mutations (52)(53)(54)(55). To determine if these effects are preserved in the context of our EGFR-retargeted HSV strain, we infected a panel of human pancreatic carcinoma cell lines (PANC-1, AsPC-1, PK-8, and BxPC-3) and examined the lateral spread of virus and cytocidal efficiency.…”
Section: Introduction Of Syncytial Mutations Into An Egfr-retargeted mentioning
confidence: 99%
“…Alternatively, essential genes of the virus can be placed under the control of tissue-specific promoters, thus limiting their replication to specific tissues. [1][2][3] Finally, therapeutic strains in which the virus thymidine kinase gene remains unmodified will still be susceptible to antiviral drugs such as acyclovir. The combination of modified viruses with chemical agents to increase their potency in tumors shows promise for use in the treatment of human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Herpes simplex virus-1 (HSV-1) is a suitable candidate virus because of its large genome with many non-essential proteins, ease of manipulation, natural oncolytic properties and wide host tropism. [1][2][3] The removal of virulence genes enhances the safety of HSV-1 vectors against serious complications and/or reversion to wild type. [4][5][6] Some of these oncolytic HSV-1 viruses have been approved for clinical trials in breast cancer, 3,7 head and neck carcinoma, 8 glioma, 9 melanoma, 10 non-small-cell lung carcinoma 11 and metastases from colorectal cancer 12 (reviewed in Manservigi et al 13 ).…”
Section: Introductionmentioning
confidence: 99%